En nombre del Gobierno: El Perú y Uchuraccay: un Siglo de Política Campesina - Fritz Culp (Vernacular: New Connections in Language, Literature, & Culture, 2020)
Review of: Del Pino, Ponciano. En nombre del gobierno: El Perú y Uchuraccay: un siglo de política campesina. Decades removed from the heights of violence and revolution in Peru, Ponciano del Pino returns to the infamous murders of eight reporters in the Andes. Unlike the normalization of daily bloodshed, village massacres and other atrocities that culminated in the loss of over 69,000 lives, these deaths managed to interrupt the numbness to the destructive war machine driven by the insurgent political party Partido Comunista del Perú—Sendero Luminoso, the Communist Party of Peru—Shining Path, and the Peruvian Armed Forces. At home and abroad, many puzzled over the community that had mistaken the eight reporters for insurgents—killing them publicly in self-defense and in support of the nation. Perhaps, the motives that drew Mario Vargas Llosa to oversee the presidential investigation are the same that intersect with del Pino’s work so many years later. The village, Uchuraccay, situated at the figurative and geographical heart of the war, offers a unique microcosm of the tensions, motivations and fears that continue to complicate our understanding of such unthinkable actions during a time of social chaos.
Keywords: review; En nombre del Gobierno; Del Pino; Perú; Uchuraccay